Participation of Swazi women in the traditional public sphere, Sibaya, in the Kingdom of Swaziland - Maxwell Vusumuzi Mthembu (Communicare)
The Kingdom of Swaziland has continued to use the cattle byre, Sibaya, for deliberations on issues of national importance. This deliberative public sphere is convened once in a while to discuss pertinent issues relating to the well-being of the Swazi nation. It is a public sphere that used to be the preserve of men but has since been opened up to accommodate women. Despite their participation, women still have to follow certain laid down rules to make their oral submissions in this space. In 2016, the King of Swaziland convened the Sibaya for seven days and thousands of citizens attended to make oral submissions on social, political, economic and cultural issues. This article focuses on the representations made by women during the 2016 meeting and their perception about this space. Qualitative content analysis was used to analyse the data on submissions, which were monitored on national television and recorded. Interviews were also conducted with some participants to find out how they feel about this space. Grounded on Fraser’s concept of the counter public sphere, the study reveals that interlocutors feel that this is a restrictive and intimidating space that is and that there are too many rules that discriminate against the free participation of women. Thorny issues raised by women pertained to education (primary, secondary and tertiary), the welfare of widows, chieftaincy disputes, access to land, provision of water and electricity and gender-based violence, among others.